Lesbian convict in women’s prison: a description of rational choice - Rahayu, Mulyani; Dermawan, M. Kemal; Susanti, Vinita; Hamzah, Imaddudin (Eximia, 2023)
Same sex behavior does not only occur in society, this behavior also occurs in prisons, include all women’s prisons in Indonesia. Conditions in prison for a long time made them interact very often and it was exacerbated by the number of inmates exceeding the occupancy capacity. Previous research, mentioning this theme is still very rarely raised considering that lesbian behavior is considered a taboo behavior to be discussed. Focus this research how the process and dynamics of lesbians in Women’s prison. With qualitative methods, and Rational Choice Theory. Data collection techniques through triangulation namely interviews with 8 informants, field observations, and literature studies. This research was conducted in two women’s prisons with overcapacity conditions. The results of the study show that the process in prisons is influenced by culture in prisons which greatly influences the occurrence of lesbian behavior. For convicts who before they entered prison were heterosexual and being homosexual in prison was rational choice. There are 2 large groupings of lesbi convicts in prison with their respective processes and dynamics as well as several factors that push them to become lesbi based on profit and loss or rational considerations.